English Essay Writing at SMA Negeri 1 Pulau Morotai - Dwi Budidarma Sutrisno; Megawati Basri; Jasmal Martora (Universitas Muhammadiyah Jember, 2025)
The objective of this current community service is to introduce and improve English essay writing skill to students at SMA Negeri 1 Pulau Morotai through four class meetings. 22 eleventh graders of high school students joined as participants throughout the whole session.. The class activities include lecture and game with one pre-test at the first meeting and one post- test at the fourth meeting. Written flashcards are integrated throughout the games in all meetings. Five topics discussed consist of vocabulary building, sentence writing, tenses writing, paragraph writing and essay writing. The result shows that (1) the students were successfully introduced to the concept of English essay writing considering the completion of all games throughout the meetings and overall increase of scores of post-test compared to pre-test, however, (2) the students’ improvements can only be heavily found on word, sentence, and tenses level questions. In order words, students’ difficulties on paragraph and essay level questions remained.